Administrative Burdens in Child Welfare Systems - EDWARDS, FRANK; FONG, KELLEY; COPELAND, VICTORIA; RAZ, MICAL; DETTLAFF, ALAN (RSF : Russell Sage Foundation journal of the social sciences, 2023)
Public policy often imposes administrative burdens that constrain people’s ability to access benefits and affirmatively exercise fundamental rights. In this article, we extend the administrative burden framework to argue that the state also places burdens on people who have involuntary contact with coercive state institutions, such as the child welfare system. Just as administrative burdens lock “undeserving,” marginalized populations out of benefits, administrative burdens also lock such populations into coercive intrusion. Drawing on interview data with system-involved mothers and child welfare caseworkers, we show how parents subject to oversight by child protection authorities must overcome substantial learning, compliance, and psychological costs or risk losing a fundamental right: the right to parent their children. We suggest that the burdens of service provision should be loaded onto governments rather than already strained and resource-deprived families.